Resolution mechanism model for heterogeneous systems in smart home environment - Mohamed, Raihani; Perumal, Thinagaran; Sulaiman, Md. Nasir; Mustapha, Norwati; Yamaguchi, Shigo (IEEE, 2018)
Emerging growth of heterogeneous devices can be seen in smart home environment. These devices are diversified and highly heterogeneous in nature. Hence, there is a need of multiple devices in the same environment are orchestrating with one another in harmonic way. However, this thing becoming complicated whenever more heterogeneous systems are introducing into the same environment from time to time. This condition leads to system dependencies with each other and eventually leading towards conflict occurrences among them. In this work, we present a conflict resolution mechanism for heterogeneous devices in home environment using Resolution Mechanism model. The performance of the proposed model verified and justified within the need of smart home context.